Deep learning the intergalactic medium using Lyman-alpha forest at 4 ≤ z ≤ 5 - Nasir, Fahad; Gaikwad, Prakash; Davies, Frederick B.; Bolton, James S; Puchwein, Ewald; Bosman, Sarah (Monthly notices of the Royal Astronomical Society, 2024)
Unveiling the thermal history of the intergalactic medium (IGM) at
Online veröffentlicht: 17. September 2024
Gesehen am 19.03.2025